Incidence of Rice Hispa, Dicladispa Armigera (Coleoptera: Chrysomelidae) on Kharif Paddy in the Agro Climatic Conditions of the Northern Parts of West Bengal, India (Global Journal of Science Frontier Research, 2012)
Incidence of rice hispa (RH), Dicladispa armigera population in paddy crop (Oryza sativa L.) field was assessed by sweep net estimation during four consecutive crop seasons (2005-2008) at Hemtabad, Uttar Dinajpur, West Bengal. The RH population was initiated at about 29 standard meteorological weeks (SMW), improved at first slowly up to 27 SMW then steadily up to 35 SMW attaining the maximum at about 36 SMW which was maintained up to about 38 SMW. The population then subsumed at first slowly up to 40 SMW then abruptly. After 43 SMW insignificant number of RH population was detected. Abiotic conditions such as maximum temperature, temperature gradient, maximum relative humidity, humidity gradient and average relative humidity had significant positive influence on D. armigera population. An insignificantly positive relation was also found with the average temperature. In case of minimum temperature, minimum relative humidity, sunshine hours and heavy rainfall, a negative influence on population development was observed.
Keywords: rice hispa incidence; climatic factors; paddy crop; seasonality